KEPALA NEGARA PEREMPUAN MUSLIMAH: ANALISIS WACANA TERHADAP TAFSIR QURAISH SHIHAB - Naqiyah Mukhtar (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
In general there are two schools of thought on whether a Muslim woman can become apolitical leader. One school forbids it, while the other allows it. This study will argue that thecontroversy surrounding womenâ€™s political leadership that exists in the Islamic discourse isnot merely a matter of isntinbÄÅ£ (deductive inquiry) regarding the meaning of Qurâ€™anic verseand tradition (al-nuÅŸÅ«ÅŸ) and the difference in dalÄ«l (reference) that is used in interpretation asstated by previous scholar, but also involves various other factors. These factors includepersonal background, ideology and audience. The data has been obtained from studying theQurâ€™anic verse (al-NisÄ` /4:34) referred to by those who prohibit female leadership. Theprimary reference is Tafsir al-Mishbah by Quraish Shihab. The data are approached by using adiscourse analysis. The standpoints expressed by this author did not happen in a vacuum, butwere influenced by the authorâ€™s perception and the ideology of the interpreter of his work.Thus the significance of this study is to show that Qurâ€™anic verses especially those allied to therole of women, can be construed in various ways that are in accordance with a particularscholarâ€™s propensities.